Machining of biocompatible materials — Recent advances. Issue 2 (2019) - Axinte, Dragos; Guo, Yuebin; Liao, Zhirong; Shih, Albert J.; M'Saoubi, Rachid; Sugita, Naohiko
Abstract: Machining of biocompatible materials is facing the fundamental challenges due to the specific material properties as well as the application requirements. Firstly, this paper presents a review of various materials which the medical industry needs to machine, then comments on the advances in the understanding of their specific cutting mechanisms. Finally it reviews the machining processes that the industry employs for different applications. This highlights the specific functional requirements that need to be considered when machining biocompatible materials and the associated machines and tooling. An analysis of the scientific and engineering challenges and opportunities related to this topic are presented.